PhET Aplication Program: Strategi Penguatan Pemahaman Pembelajaran Jarak Jauh pada Materi Radiasi Benda Hitam melalui Percobaan Berbantu Lab Virtual dan Media Sosial - Ida Puspita (Jurnal Pendidikan Madrasah, 2020)
This research aims to improve the understanding of black matter radiation by utilizing the PhET circuit-construction-kit-ac application in remote learning using Whatsapp social media, as well as utilizing virtual labs. This article is the best practice carried out in the even semester of 2019/2020 lesson in the students of the class XII IPA. The implementation of this learning strategy has a positive achievement, among others: 1) understanding and problem solving black objects radiation with distance learning becomes easier; 2) as a solution for conducting experiments in the application of distance learning that can be done online or offline; 3) can display real and visual radiation experiments of black objects and easy to operate; 4) Use of PhET circuit-construction-kit-ac based on basic concepts, rules or principles, prevailing agreements, and use of reasoning; 5) There are no constraints while implementing PhET circuit-construction-kit-ac in distance learning; 6) Training students' independence. The results showed: a) the presence of test solutions in distance learning; b) Students are more enthusiastic, with indications of collecting timely assignments, all the tasks provided completed by all students; c) Students can match the final test results using the PhET circuit-construction-kit-ac with qualitative calculations using the prevailing black-object radiation equation; and d) The increasing learning outcomes are quite significant.